2015
DOI: 10.1080/17470919.2015.1017112
|View full text |Cite
|
Sign up to set email alerts
|

Negative emotions impact lateral prefrontal cortex activation during theory of mind: An fNIRS study

Abstract: The lateral prefrontal cortex (lPFC) plays a critical role in inhibiting self-perspective information, which is necessary for theory of mind (ToM) processing. Additionally, previous research has indicated that negative emotions interfere with lPFC activation during executive tasks. In this study, we hypothesized that negative emotions would inhibit lPFC activation during a ToM task. While female participants performed the director task following the observation of emotionally laden movies (neutral/negative/pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…Indeed, additional evidence suggests that the VLPFC is involved in affective ToM processing (e.g., the faux pas task) 21 27 28 29 , while the DLPFC is involved in the processing of cognitive ToM (e.g., the false belief task) 30 31 . These studies provide converging evidence that a functioning ToM is supported by regions outside of those traditionally considered to comprise the ToM network, which consists of such as posterior superior temporal sulcus, inferior frontal and parietal cortex, and anterior rostral medial prefrontal cortex 32 , and that the lateral PFC is one of those newly identified regions 24 33 . Furthermore, lesion studies have highlighted the key role of prefrontal and frontal brain areas in ToM function 34 35 36 37 38 .…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Indeed, additional evidence suggests that the VLPFC is involved in affective ToM processing (e.g., the faux pas task) 21 27 28 29 , while the DLPFC is involved in the processing of cognitive ToM (e.g., the false belief task) 30 31 . These studies provide converging evidence that a functioning ToM is supported by regions outside of those traditionally considered to comprise the ToM network, which consists of such as posterior superior temporal sulcus, inferior frontal and parietal cortex, and anterior rostral medial prefrontal cortex 32 , and that the lateral PFC is one of those newly identified regions 24 33 . Furthermore, lesion studies have highlighted the key role of prefrontal and frontal brain areas in ToM function 34 35 36 37 38 .…”
Section: Discussionmentioning
confidence: 87%
“…Supporting this, studies have reported that the PFC functions not only in working memory, but also in the regulation of social and emotional behaviors 20 . More specifically, recent neuroimaging studies suggest that both the lateral and medial PFC are particularly important for ToM 21 22 23 24 . ToM is the mentalizing capacity to infer the mental states of others, including their thoughts, desires, and intentions 25 .…”
Section: Discussionmentioning
confidence: 99%
“…The left OFC and right OFC are asymmetric in response to negative emotions, and the left OFC is more sensitive to negative emotion (Himichi et al, 2015). Therefore, we delivered the drugs into the left OFC, and we also compared the effects of the left OFC infusion with bilateral OFC infusions on depressive behaviors.…”
Section: Surgerymentioning
confidence: 99%
“…EEG findings have suggested that subjects remain aroused after emotional narratives (Borchardt et al, 2018 ). Finally, negative emotions induced by movie clips inhibited lateral prefrontal cortical activation during a subsequent theory of mind task (Himichi et al, 2015 ). Together, these findings indicate that emotionally engaging narratives shape subsequent information processing in the brain.…”
Section: Emotional Valence and Arousal During Narratives Differentialmentioning
confidence: 99%